Audio lingual strategies to teach basic english phonological production of the /F/, /V/, /S/ and /Z/ fricative sounds anibg 12th graders at Volcan Hight School - Caballero, Carol (UDELAS, 2013)
Whit the appearance of the english language, a series of theories and methods hace arisen and which objective is to ease strategies and techniques for teaching english. Those methods based in the auditory development.